Translating the Daughter’s Consciousness in Genni Gunn’s Tracing Iris - Seccia, Maria Cristina (Italian Canadiana, 2023)
This article examines Genni Gunn’s novel Tracing Iris (2001) and its Italian translation Alla ricerca di Iris (2022) with a focus on the representation of the mother-daughter relationship, a recurring theme in Italian-Canadian women’s writing and a fruitful object of investigation in Translation Studies as it offers new insights into women’s writing and the crucial role played by the maternal figure in the formation of female identity. Unlike most Italian-Canadian daughter-centric first-person narratives, which commonly represent a conflictual relationship with the Italian maternal figure, seen as the embodiment of Italian culture, Tracing Iris is a third-person narrative whose omniscient narrator presents an absent mother and a daughter searching for her. However, what will be shown here is that the narrator’s point of view, in fact, still relies on the fictional daughter’s consciousness. In light of Translation Studies scholars arguing that the narrative point of view inevitably undergoes changes in translation, this analysis will show whether the fictional daughter’s consciousness is still reflected in Alla ricerca di Iris. Five source- and target-text passages will therefore be scrutinized with a focus on the translator’s lexical choices and any changes that these might have implied.